Effect of dimple shape, occupancy, and volume ratio on aerodynamic characteristics of golf balls during rotation - Kohei MORIYAMA; Hiroo OKANAGA (Nihon Kikai Gakkai ronbunshu, 2023)
The surface of a golf ball is provided with innumerable dents called dimples to improve the flight distance. In this study, we manufactured 15 model balls in which the dimple occupancy and the dimple volume ratio was changed by the dimple diameter and the number of dimples, and the dimple shapes. Using these balls, we carried out lift and drag measurements of the rotating balls in wind tunnel experiments. Then, a flight trajectory simulation was performed based on the obtained experimental results. As a result, the influence of the base shape showed different results for both drag and lift coefficients for each occupancy. However, the drag coefficient decreased and the lift coefficient increased as the dimple volume ratio increased regardless of the dimple shape. In addition, the relationship between the lift-drag ratio and the dimple volume ratio showed that the lift-drag ratio decreased as the dimple volume ratio increased. The flight trajectory simulation results showed that the flying distance was greater for O=52.6% and O=63.1% with a conical base when the dimple volume ratio was small and the dimple depth is DD/d=4.55×10-3. Two spheres with a spherical base and a conical base at O=83.1%, also exhibited similar flying distances. However, the flight distance tends to increase as the dimple volume ratio decreases. The ball's trajectory was lower when the volume ratio was small, and higher trajectory was obtained when the occupancy ratio was high.